2012
DOI: 10.1590/s0102-79722012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Memories and prevalence of posttraumatic stress disorder in intensive care units

Abstract: The present study evaluated the prevalence of PTSD indicators in patients who had to be hospitalized in ICU six months after being discharged and examined the relationship between PTSD and mnemonic memories. Participants were 41 adult patients with different diseases who answered questionnaires about PTSD, memory and clinical information. It was identified that 24.4% of the sample presented PTSD symptoms. These patients presented more affective memories than those without PTSD (t=2.29, p<.05). Affective memori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
0
10
1
5
Order By: Relevance
“…Patients might even wrongly but clearly recall that the nurses or physicians had intended to kill them 13 . Therefore, as the findings of recent studies have shown, 14,15 patients' memories of the ICU can be associated with the occurrence of PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Patients might even wrongly but clearly recall that the nurses or physicians had intended to kill them 13 . Therefore, as the findings of recent studies have shown, 14,15 patients' memories of the ICU can be associated with the occurrence of PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Today, with advances in technology and medical equipment, mortality rate of patients is reduced. However, patients discharged from critical care units might have high rates of physical and psychological complications ( 3 , 4 ). Psychological disorders such as depression, anxiety and PTSD are some of these complications ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A semelhança nos níveis de TEPT entre jovens do sexo feminino e masculino nesta amostra é diferente dos resultados de outros estudos que avaliaram TEPT em outras situações de problemas de saúde (Girard et al, 2007;Rovatti, Teodoro, & Kern de Castro, 2012;Schelling, 2007), que indicavam maiores índices nas mulheres. Em estudos com sobreviventes de cancro infantil, alguns autores encontraram um índice maior de TEPT em mulheres Psychology, Community & Health 2015, Vol.…”
Section: Discussionunclassified